THE USE OF INFORMATION COMMUNICATION TECHNOLOGY (ICT) AS THE TECHNOLOGY ACCEPTANCE MODEL (TAM) OF MOBILE BANKING - Paulus Yokie Radnan; John Tampil Purba (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
Information Technology services in banking business which is very dynamic and advanced makes the bankers must adjust to the presence of this technology. In this paper, the authors will explain the role of Mobile banking technology which is provided by CIMB Niaga in servicing its customers for banking transactions. The methodology used in this paper is quantitative with the purposive sampling one. Instrument used the Technology Acceptance Model (TAM) as developed by Parasuraman and Davis by modifying them to fit the state of the research object. This research was conducted in Jakarta and several other places. Research and data collection took 6 months from November 2015 to April 2016. The variables included trust, perceived use (PU), perceived ease of use (PEU), attitude toward use (ATU), Intent to use (ITU), and actual use (AU). After the data were collected, the regression analysis was performed. From the analysis result it was found that trust and perceived use (PU) variables did not positively and significantly influence the intent to use (ITU) variable, as well as the perceived use variables (PU) and perceived ease of use (PEU) which have no significant and positive effect on attitude variable on usage (ATU). For that case, the authors propose an improvement strategy to maintain and grow this business forward.